A Hybrid Vision/Force Control Strategy for Handheld Robotic Devices Enhancing Probe-Based Confocal Laser Endomicroscopy - Ingu Choi; Eunchan Kim; Yang, Sung wook (IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2024)
We introduce a novel hybrid vision/force control strategy for robotic devices designed to obtain clear and consistent images using probe-based confocal laser endomicroscopy (pCLE). Due to the variable nature of tissue characteristics encountered during pCLE imaging, the conventional approach of pre-setting forces or focus metrics for either force or vision control is often impractical and inadequate. To address this, our strategy employs a blur metric called the CR score to assess the level of blur in pCLE images, enabling the attainment of clear and focused images. At the onset of a pCLE scan, the system autonomously determines the target CR score for vision control, in tandem with a real-time peak detection algorithm. Concurrently, force control is applied judiciously to prevent excessive force on the tissue, adjusting to ensure minimal force is applied, thus preserving image focus. This innovative approach facilitates seamless transitions between vision and force control, depending on the imaging conditions, thereby ensuring the acquisition of consistent pCLE images with minimal force. Our method marks a notable improvement over conventional PID force control techniques. By dynamically adjusting target forces and minimizing force application during operation, we not only enhance the precision and quality of pCLE imaging but also eliminate the dependency on manual pre-settings.